Instituições de ensino superior católicas: ainda tem sentido? Percepção e aceitação de alunos da cidade do Recife-PE. - Torres, Maria de Fátima da Nóbrega (2021)
The demands of the current job market have led to a culture of efficiency and productivity, which require from universities an excessive attention to the intellectual capacity of the student. However, there are institutions that were not intimidated by this new scenario; among them, Catholic Higher Education Institutions (CHEIs) that, due to their religious nature, seek to keep their pedagogical-Christian mission alive with the purpose of offering integral training to its students considering, in addition to their intellectual dimension, the moral, spiritual, and religious ones, awakening in them a humanistic essence. Nevertheless, the present scenarios have revealed many challenges to carry out a mission of this nature, leading to the question of whether this purpose still makes sense. Following the trajectory of Church´s relationship with the education of Antiquity until nowadays and deepening the studies on the mission of ( CHEIs) and the challenges faced by these institutions, it was possible to elaborate the thesis that the students surveyed perceive the pedagogical-Christian mission of their Catholic Higher Education Institution, as well as accept this mission for the present day, which would confirm that it makes sense to maintain a mission such as the one proposed by the CHEIs.Thus, as a way of contributing to this discussion, this study aimed to learn about the perception and acceptance of students from Catholic Higher Education Institutions regarding the pedagogical-Christian mission of their institution today. The work is constituted of the introduction and the following four chapters being three the form the theoric framework with quotes of authors in the field of education as Manacorda, Luzuriaga and Nunes,in addition to others who study the mission of CHEIs as Miranda and Juliatto. The study is characterized as exploratory-descriptive and was carried out with 302 students from three CHEIs in Recife. The results of the research confirm the thesis proposed above and feed the hope that, even in the face of a culture of materialism, it is possible to promote the integral development of students, a quality so necessary in contemporary society.